2013
DOI: 10.1007/s12020-013-9928-8
|View full text |Cite
|
Sign up to set email alerts
|

Raised serum TSH in morbid-obese and non-obese patients: effect on the circulating lipid profile

Abstract: Morbid obesity is associated with a high rate of raised serum TSH associated with normal free thyroid hormones. The body repercussions of this thyroid abnormality, suggesting subclinical hypothyroidism, are still debated. In particular, it is unclear whether the raised serum TSH of obesity results in changes of circulating lipids typically observed in hypothyroidism. Aim of this study was to evaluate the impact of a raised serum TSH on the lipid profile in morbid-obese and non-obese patients. Serum TSH, FT4, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…A previous study demonstrated that in subjects with morbid obesity, serum cholesterol levels were lower than in lean controls with similar degrees of serum TSH elevation, which suggests that a higher serum TSH level in subjects with morbid obesity is not associated with peripheral hypothyroidism . In our study, TC, HDL‐C and LDL‐C were similar in the upper and lower TSH quantiles.…”
Section: Discussionsupporting
confidence: 73%
“…A previous study demonstrated that in subjects with morbid obesity, serum cholesterol levels were lower than in lean controls with similar degrees of serum TSH elevation, which suggests that a higher serum TSH level in subjects with morbid obesity is not associated with peripheral hypothyroidism . In our study, TC, HDL‐C and LDL‐C were similar in the upper and lower TSH quantiles.…”
Section: Discussionsupporting
confidence: 73%
“…It was found that autoimmune hypothyroidism is more prevalent in patients with minor degrees of weight excess (66), whereas slightly increased serum levels of TSH, being unrelated to thyroid autoimmunity, predominate in morbidly obese patients (64). In morbid obese subjects, the serum concentration of cholesterol was lower than in lean controls having similar degrees of serum TSH elevation (76). This finding suggests that the higher serum TSH of morbid obese patients is not associated with peripheral hypothyroidism.…”
Section: Thyroid Function and Structure In Obese Subjectsmentioning
confidence: 94%
“…However, Rotondi reported on a study of 28 morbidly obese patients with SCH (BMI ≥ 40 kg/m 2 ) and found that this group had significantly lower rates of elevated antithyroid antibodies when compared with 56 normalweight patients with SCH (32.1% vs. 66.1%, respectively; p < 0.005), which suggests that the increased TSH levels associated with morbid obesity may not indicate true thyroid dysfunction (52). More recently, the same researchers provided further evidence that the TSH elevations associated with obesity are not diagnostic of hypothyroidism, emphasising the need for a multifaceted approach to diagnosis, when they found lower lipid levels in morbidly obese vs. non-obese individuals with similar TSH elevations (53). A review of this topic noted that the moderate TSH elevations observed with obesity is generally associated with triiodothyronine levels higher than expected, resulting in an increase in resting energy expenditure consistent with an adaptive process (53,54).…”
Section: Obesitymentioning
confidence: 99%